Gemcitabin im Modell der akuten und akzelerierten Transplantatabstossung - Jung, Florian Johannes; Justus Liebig University Giessen (My University, 2003)
Das Nukleosid-Analogon Gemcitabin (Gemzar®), bisher nur als Zytostatikum gegen eine Vielzahl von Tumoren verwendet, konnte in der vorliegenden Studie erfolgreich als potentes immunsuppressives Medikament im Rahmen einer akuten und akzelerierten Transplantatabstoßung im Rattenmodell eingesetzt werden.In der Dosierung von 130-150 µg/kg KG/d unterdrückte Gemzar® die akute und akzelerierte Abstoßung von allogenen (LBNF1->LEW) Nieren- und Herztransplantaten signifikant gegenüber der nicht behandelten Gruppe (Transplantatüberlebenszeiten: akut Niere 68,17±42,99 vs. 5,9±0,64 p<0,005; akut Herz 32,13±15,37 vs. 7±0;63 p<0,003; akzeleriert Herz 5±1 vs. 1,39±0,13 p<0,001).In vitro konnten die durch allogene Antigene ausgelöste Proliferation der Lymphozyten im MLR-Test in der mit Gemcitabin behandelten Gruppe deutlich herabgesetzt werden. Durch Zytotoxizitätstest, radiale Immundiffussion und FACS-Analyse war es möglich, eine Inhibition der durch NK-Zellen ausgelösten Zell-Lyse, eine verminderte Produktion der Gesammt-Immunglobuline sowie die vollständige Abrogation allospezifischer IgM- und IgG-Antikörper in der experimentellen Gruppe zu zeigen. Innerhalb der physiologischen Zeitspanne einer akuten Transplantatabstoßung konnte durch die PCR-Analyse gezeigt werden, dass mit Gemcitabin die mRNA-Transkriptexpression innerhalb des Transplantates von IFN-?, CD 3 und CD 25 im Vergleich zur Kontrollgruppe deutlich reduziert wird.Die Ergebnisse aus dieser Studie versprechen eine weitere Einsatzmöglichkeit des Zytostatikums Gemcitabin im Rahmen immunsuppressiver Therapie nach Organtransplantation. Weitere Studien, insbesondere zur Dosisoptimierung und zur Anwendung in der Kombinationstherapie sind erforderlich und in Vorbereitung.

The 2´, 2´-DIFLUORODEOXYCYTIDINE (dFdC, gemcitabine) is a novel chemotherapeutic agent for treatment of a diversity of solid tumors. Incorporation intoDNA of the phosphorylated triphosphate of dFdC inhibits DNA-synthesis and leads to cell death. Recently, dFdC has been shown to inhibit acute rejection of cardiac allografts inrats, significantly prolonging transplant (Tx) survival. This prompted us to further investigate the immunosuppressive effect and mechanism of dFdC in models of experimental organ rejection. MATERIALS AND METHODS Transplantation Models For acute rejection, LEW recipients received cardiac or renal allografts from LBNF1 donors. Hearts were heterotopically placed and microsurgically anastomosed to the abdominal great vessels. Left renal allografts were end-to-end anastomosed and positioned orthotopically.Without treatment, transplanted organs were rejected within 7 to 8 days. Cardiac function could easily be monitored by palpation. After nephrectomy of the syngeneic kidney on day 7 posttransplantation, renal graft performance was determined by survival. For accelerated rejection (ACCR) LEW recipients were sensitized with BN skin transplants 7 daysbefore heterotopic engraftment of a LBNF1 heart. In untreated controls, rejection occured within 24 to 36 hours. Treatment Treated recipients received 130 to 150 µg/kg of dFdC daily subcutaneously starting at the day of organ (acute models) or skin (ACCR model) transplantation. Assays Mixed lymphocyte reaction and cytotoxicity assays were previously described.3 Assessment of circulating total. (Turbiquant, Dade Behring, Marburg, Germany) and allospecific (as described3) immunoglobin (Ig) IgM and IgG was performed. RESULTS Gemcitabine therapy abrogated acute rejection of heterotopic cardiac and orthotopic renal Tx, significantly prolonging graft survival. In LEW recipients of LBNF1 cardiac grafts (n = 8) receiving 130 µg/kg per day dFdC subcutaneously, the mean organ survival was 37.1 ± 13.6 days (P <0.003). In orthotopic renal grafts (n =5) in the same donor/recipient combination treated with 150 µg/kg per day, dFdC transplant survival was 69.5 ± 40.1 days (P < 0.001).In a model of ACCR, where LEW recipients, sensitised with BN skin transplants (day -7) were treated, starting at time of skin Tx, with 150 µg/kg per day dFdC, gemcitabineabrogated ACCR in all treated animals (n = 7), extending Tx survival from 24 to 36 hours to 5 ± 0.9 days (P < 0.0001). We analyzed the total circulating IgM and IgG in recipientsof kidney and cardiac allografts. For either graft, both Ig classes were significantly suppressed for more than 21 days posttransplantation (cardiac Tx: P < 0.02 IgG/M; renal Tx: P<0.02/.007 IgG/M). Analysis of allospecific Ig following transplantation showed a complete and lasting abrogation of both IgM and IgG antibodies (data not shown). MLR showed decreased relative proliferation indices (0.21, 0.32) with complete inhibition of cytotoxicity (n = 4) in the treated recipients at day 6 posttransplantation. CONCLUSION Gemcitabine is a potent novel immunosuppressive agent that abrogates acute and accelerated rejection. During therapy with dFdC, no allospecific antibodies could be detected, and total Ig titers were markedly decreased in recipients. Cytotoxicity was abrogated, and T-cell proliferative responses were down-regulated. Initially viewed as a chemotherapeutic drug, gemcitabine may well serve as a promising novel immunosuppressive adjunct in antirejectiontherapy in transplantation medicine.
Keywords: Transplantation; Immunsuppression; Gemcitabin; Transplantation; Immunosuppression; Gemcitabine; ddc:610